A survey into the utilization of probiotics and medicinal plants among individuals afflicted with gastrointestinal disorders in healthcare institutions in Saïda, Algeria - Lamia Abir Tazi; Yasmina Benabdesslem; Sabrina Amara; Kadda Hachem (Libyan Journal of Medicine)
Aim: Functional gastrointestinal (GI) disorders are recognized as a major public health concern worldwide. These disorders involve persistent digestive symptoms indicative of digestive tract dysfunction.Materials and Methods: A survey examining the utilisation of probiotics and medicinal plants as supplementary treatments was conducted on 160 patients with GI disorders at healthcare institutions in Saïda from March to April 2023 using questionnaires that had been previously adapted and tested for reliability with Cronbach’s alpha test. Raw data collected through the questionnaires were transferred to a database and analysed using SPSS software.Results: Overall, 49.38% of participants possessed knowledge of or actively utilised probiotics; such awareness was strongly associated with the participants’ educational attainment (p = 0.029). The noteworthy probiotic supplements were Biocharbon (36.09%), Lactocil (15.38%), Smebiocta (13.61%), Ultrabiotic Adult (12.43%), Effidigest (12.43%), and Ultralevure (7.69%). During crisis, individuals tended to consume natural goods rich in probiotics, including yoghurt (13.26%) and fermented milk (8.60%), as well as foods rich in prebiotic fibre, including vegetables (18.99%), fruits (13.26%), wheat (9.67%), bran (7.52%), rye (6.81%), and oat flakes (6.45%). Additionally, 77.56% of patients used medicinal plants during crises, with Mentha spicata (12.2%), Thymus vulgaris (11.3%), Pimpinella anisum (8.5%), Cuminum cyminum (8.0%), Punica granatum (7.8%), Trachyspermum ammi (7.5%), and Senna acutifolia (7.0%) being the more commonly favoured options in phytotherapy. The main focus of these herbs was to alleviate bloating (57%), constipation (30.12%), and diarrhoea (12.87%) (p < 0.001). The most frequently utilised plant parts were leaves (47.30%), seeds (25.21%), and bark (13.21%). Most patients (82.91%) favoured infusion as their preferred consumption method, and approximately 85.43% believed in phytotherapy’s ability to extend symptomatic relief.Conclusion: The understanding of probiotics is still in its infancy, whereas phytotherapy is more widely accepted by patients. Nonetheless, patients are open to the exploration of natural alternatives to conventional medicines.